Coastal wave-energy attenuation by artificial wooden fences deployed for mangrove restoration: an experimental study - Shu, Anping; Zhu, Jiapin; Cui, Baoshan; Wang, Le; Zhang, Ziru; Pi, Chengling (Frontiers in Marine Science, 2023)
By offering natural protection along offshore wetlands, mangroves play a crucial role in providing great ecological and economic benefits to local communities. However, mangroves are currently facing an increasing threat of decline worldwide from widespread human activities and climate change. Recently, eco-friendly structures have been deployed along eroded coasts for mangrove restoration projects, and these structures have the capability to attenuate incoming waves and strengthen sediment deposition in new habitats for mangrove colonization and persistence. However, the design and performance of the fences used can differ substantially among different projects, therefore, it is necessary to study the major factors affecting the wave dissipation performance of these fences and find out a more effective structural design. Thus, we focus on using two distinct types of fences with and without porous infills to study the function of infill porosity and frame density, and experiments of waves passing through the fence obstacles were carried out in a wave-generated flume 0.8 m wide and 25 m long, in which nine wooden fences with varying infill porosities (0.60 0.90) and frame densities (0.40 and 0.70) were predetermined to measure the wave transmission, reflection and wave dissipation. In total, 180 experimental runs were conducted under 18 wave conditions with different water depths, wave heights and periods. The results showed that the fence with a lower infill porosity appears to increase wave transmission coefficient that comes at a cost of a higher reflection coefficient and less wave energy dissipation inside the fence, and the fence with the highest porosity infills (90%) is nearly equivalent to the fence without any infills but a dense frame in terms of wave damping performance. Moreover, both wave transmission coefficient and bulk drag coefficients of the structure can be remarkably affected by the incoming wave steepness. These results are significant basis for not only attenuating massive destructions from incoming waves but also guiding the design of mangrove restoration projects in offshore wetlands.